PENGARUH PENGELUARAN PEMERINTAH BIDANG PENDIDIKAN DAN KESEHATAN TERHADAP INDEKS PEMBANGUNAN MANUSIA (IPM) PADA KAWASAN PERBATASAN NEGARA PROVINSI KALIMANTAN BARAT TAHUN 2010-2019 - Iva Ashari Ananda; U. Sulia Sukmawati; Erdila Kidrian (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2021)
The construction of an area is of concern to the government, especially in the border region that became the main manifestation of the sovereignty of the territory of a country. The Human Development index (HDI) is one of the benchmarks see the performance of the government in the effort to build the quality of human life. This study aims to analyze the influence of government spending for education and health on the HDI in the regency of West Kalimantan Province of years 2010-2019. The research method using quantitative approach with the type of library research. Source of data used is secondary data obtained from the Central Statistics Agency (BPS) of West Kalimantan Province and the Ministry of Finance of the Republic of Indonesia by using the technique of multiple regression analysis of panel data, i.e. the joint between the data time series (time series) in the period of the year 2010-2019 and data cross of the 5 districts in the border region of the country in the Province of West Kalimantan ( Kabupaten Sambas, Kabupaten Bengkayang, Kabupaten Sintang, Kabupaten Sanggau and Kabupaten Kapuas Hulu). The results of research in multiple regression showed Y = 6129,742 - 0,000267 X1 + 0,002 X2, for the t test (partial) shows that the variable X1 is the government spending the field of education is not significant effect on HDI in the district of the state border of the Province of West Kalimantan years 2010-2019. However, in the variable X2 that government spending health effect singnifikan on the HDI in the district of the state border of the Province of West Kalimantan years 2010-2019. The magnitude of the influence of government spending for education and health on the HDI seen from the R-square, i.e. 0.600 that the variables X1 and variable X2 effect on Y by 60% and the remaining 40% is influenced by other factors not examined in this study. In the F test (simultaneous), based on the results in the ANOVA table shows that the significance value of 0.000<0.05. So berdasarhkan the hypothesis that H3 is accepted. Thus the independent variables X1 and X2 affect the variable Y so that the result is government spending for education and health effect on the HDI in the district of the border Province of West Kalimantan years 2010-2019.